A wearable sensor based on janus fabric upon an electrochemical analysis platform for sweat glucose detection - Ren, Jianing; Li, Qiujin; Feng, Kexin; Gong, Jixian; Li, Zheng; Liu, Xiuming; Yang, Li; Zhang, Jianfei (Talanta (Oxford), 2025)
Wearable sweat sensing devices have drawn much attention due to their noninvasive and portable properties, which is emerging as a promising technology in daily healthiness assessment issues. A sweat sensor based on Janus fabric and electrochemical analysis is proposed in this work. Unidirectional moisture transported behavior of the Janus fabric serves as the quick-drying component directly contacting skin to transfer sweat toward the detection site. The working electrode was treated by repeated activation of Prussian blue followed by chitosan/single-wall carbon nano tubes/glucose oxidase deposition, ensuring the high electrochemical activity and sensitivity to detect the sweat glucose level. A detection system was established based on the electrochemical analysis of this sweat sensor, which can provide accurate glucose level in the testing samples. The limit of detection (LOD) of the sensor for glucose was 15.32 μM (S/N = 3) and the sensitivity was 3.35 μA/mM. One male subject wears this sensor for intermittent intensity training, outputting the real-time changes in sweat glucose levels, which is consistent with the energy consumption and metabolic status during human exercise. And the sweat glucose level for different subjects was tested to be 35–135 μM, which is coincident with the distribution range of normal human sweat glucose levels. [Display omitted] •A Janus fabric works as the unidirectional moisture transported component for fast-drying sweat transfer and collection.•PB/CS/SWCNTs-modified electrode works as the detection component for sweat monitoring with high activity and sensitivity.•Sweat glucose level can be detected exclusively in high accuracy by this sensor without interference from other biomarkers.